Telocytes in normal and keratoconic human cornea: an immunohistochemical and transmission electron microscopy study. Issue 12 (17th July 2017) - Marini, Mirca; Mencucci, Rita; Rosa, Irene; Favuzza, Eleonora; Guasti, Daniele; Ibba‐Manneschi, Lidia; Manetti, Mirko
Abstract: Telocytes (TC) are typically defined as cells with telopodes by their ultrastructural features. Their presence was reported in the interstitium of various organs in vertebrates, including humans. However, no study has yet described the presence of TC in the human eye and in particular, within the stromal compartment of the cornea. To address this issue, samples of normal and pathologic (keratoconic) human corneas were tested by immunohistochemistry for CD34, platelet‐derived growth factor receptor α (PDGFRα) and c‐kit/CD117 or examined by transmission electron microscopy. We found that TC coexpressing CD34 and PDGFRα were distributed throughout the whole normal corneal stroma with different TC subtypes being distinguishable on the basis of the expression of the stemness marker c‐kit ( i.e . c‐kit‐positive and c‐kit‐negative TC subpopulations). Transmission electron microscopy examination confirmed the existence of spindle‐shaped and bipolar TC typically displaying two long and thin moniliform telopodes establishing intercellular contacts formed by gap junctions. Keratoconic corneas were characterized by ultrastructural damages and patchy loss of TC with an almost complete depletion of the c‐kit‐positive TC subpopulation. We propose that TC may contribute to the maintenance of corneal stromal homoeostasis and that, in particular, the c‐kit‐positive TC subtype might have stemness capacity participating in corneal regeneration and repair processes. Further studies are needed to clarify the differential roles of corneal TC subtypes as well as the possible therapeutic applications of TC in degenerative corneal disorders such as keratoconus.